Analisis Laporan Keuangan Pemerintah Daerah Kabupaten Subang - Farida, Ai Siti; Nugraha, Raden Faisal Maulana (Department of Public Administration, 2019)
The existence of regional autonomy requires each region to manage its finances independently. In its financial management, in 2014-2017 Subang District had several problems such as, the largest income was still from the balanced fund which was a transfer from the Central Government, low capital expenditure, regional financial growth was at a very low value and inefficient local revenue. This study aims to find out how the financial performance of the Subang Regency Government in 2014-2017 was measured using regional financial ratios. This research is a qualitative descriptive study. In data collection, researchers used the method of observation, interviews, and documentation. The type of data used is primary data from the Subang District Government Budget Realization Report 2014-2017. The results of the analysis show that the Financial Performance of the Subang Regency Government in terms of (1) The independence ratio shows that Subang Regency is very independent because the average is 17.1% (2) The harmony ratio of the Subang Regency government is more likely to prioritize operational expenditure than capital expenditure. Large operating expenses are at an average of 73.75%. While for capital expenditures at an average of 21.75% (3) Regional financial growth ratios can be said to be still very low, because the average is 8.6% (4) The efficiency ratio of local revenue can be said to be inefficient, because the average the efficiency rate is 63.3% (5) The effectiveness ratio of Subang Regency's original income has been effective, because the average effectiveness is above 100% which is 113.8%.